2012
DOI: 10.4028/www.scientific.net/ast.81.96
|View full text |Cite
|
Sign up to set email alerts
|

Super-Hydrophilic PDMS and PET Surfaces for Microfluidic Devices

Abstract: In this work the effect of air plasmas on wettability of Polydimethylsiloxane (PDMS) and polyethylene terephthalate (PET) was studied. These polymers are widely used materials in the fabrication of microfluidic devices. The microfluidic system fabricated from native PET and PDMS requires active pumping mechanism, due to a low hydrophilic surface behavior. To render hydrophilic and increase the capillary flow into the device, plasma treatments can be used. Air plasma treatment is an interesting technology for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Different kind of plasmas have been used to modify the surface of PDMS. Bartali et al [25] used air plasma to render the surface more hydrophilic and Jokinen et al [26] used oxygen and nitrogen plasma to reduce in efficient mode the contact angle on various polymers including the PDMS. Argon plasma at 100 W was successfully used by Pinto to improve the wetting properties of PDMS for bio-applications [27].…”
Section: Methodsmentioning
confidence: 99%
“…Different kind of plasmas have been used to modify the surface of PDMS. Bartali et al [25] used air plasma to render the surface more hydrophilic and Jokinen et al [26] used oxygen and nitrogen plasma to reduce in efficient mode the contact angle on various polymers including the PDMS. Argon plasma at 100 W was successfully used by Pinto to improve the wetting properties of PDMS for bio-applications [27].…”
Section: Methodsmentioning
confidence: 99%
“…The use of air plasma is convenient, and has been used to make the PDMS surface hydrophilic. 12,[21][22][23] Chen and Lindner have studied the stability of hydrophilicity on air plasma-treated PDMS surfaces. 12 Air plasma-treated PDMS-PDMS bonding, although well-known for its suitability to many microuidics applications, 24 has yet to be directly evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Surface plasma treatments have been widely used to change the surface wettability of PET and other polymers; they involve both surface abrasion and chemical changes, induced by species present in the plasma. Indeed, the plasma‐treated surface can be superhydrophobic or superhydrophilic, depending on the plasma species and conditions used 21–24 . For example, Fernández‐Blázquez et al 21 found that the PET surface became superhydrophilic on using an oxidative plasma but became superhydrophobic when the surface was fluorinated.…”
Section: Introductionmentioning
confidence: 99%